Streptococcus Pneumonia Phytotherapy - Mehrdad Karimi (Journal of Global Pharma Technology, 2017)
Streptococcus pneumoniae belongs to gram-positive coccus family of Streptococcaceae from Streptococcus viridans group. Streptococcus pneumoniae is a bacterium that causes infections such as sinusitis, ear infection and earache, septicemia, pneumonia, and meningitis. Plants are rich sources of bioactive compounds, hence are effective in a wide variety of diseases. Paying special attention toward more medicinal herbs is due to the promising effects of plants in prevention and/or treatment of diseases. The present review is in fact a report of the most effective medicinal plants on Streptococcus pneumonia. In this research, search was carried out by using the key words such as bacteria, Streptococcus pneumoniae and medicinal plants. Databases of Web of Science, PubMed, Scopus, Google Scholar, and Science direct were used to search, and related articles were used to review. Based on the results of the review on the texts, 13 medicinal herbs are the most important herbs with antibacterial properties against Streptococcus pneumonia.Keywords: Streptococcus pneumoniae, Herb, Antibacterial.